2016
DOI: 10.5535/arm.2016.40.3.496
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Characteristics of Pronator Quadratus Muscle: A Cadaver Study

Abstract: ObjectiveTo identify the anatomic characteristics of the pronator quadratus (PQ) muscle and the entry zone (EZ) of the anterior interosseous nerve (AIN) to this muscle by means of cadaver dissection.MethodsWe examined the PQ muscle and AIN in 20 forearms from 10 fresh cadavers. After identifying the PQ muscle and the EZ of the AIN, we measured the distances from the midpoint (MidP) of the PQ muscle and EZ to the vertical line passing the tip of the ulnar styloid process (MidP_X and EZ_X, respectively) and to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
1
6
2
Order By: Relevance
“…20,21 Cadaveric studies have shown equal length measurements of the PQ muscle between right and left hands. 22,23 The thickness of the PQ muscle could be bigger on the dominant side. 19 We have not found studies questioning the difference in length of the PQ muscle between dominant and nondominant hands, and there is no evidence to suggest the length of the PQ muscle differs between hand dominance.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Cadaveric studies have shown equal length measurements of the PQ muscle between right and left hands. 22,23 The thickness of the PQ muscle could be bigger on the dominant side. 19 We have not found studies questioning the difference in length of the PQ muscle between dominant and nondominant hands, and there is no evidence to suggest the length of the PQ muscle differs between hand dominance.…”
Section: Introductionmentioning
confidence: 99%
“…A residual rotational deformity should be suspected in a patient with distal diaphyseal radius fracture who manifests restriction of forearm supination, despite a mild-to-moderate angulation deformity on plain x-ray. In this study, because all deformity sites were located in the distal fifth of the malunited radius, which is the proximal insertion site of the pronator quadratus muscle, 17 pronation deformity may have occurred because of the contraction of that muscle.…”
Section: Discussionmentioning
confidence: 94%
“…They described a two-bundle method of isometric IOM reconstruction allowing for anatomical reconstruction of the oblique nature of the IOM. Based on an anatomical study by Choung et al. (2016), this technique places the ulnar insertion (distal end) of the reconstructed tendon at 24% and ulnar insertion (proximal end) of the reconstructed IOM at 33% when compared with the length of the ulna.…”
Section: Discussionmentioning
confidence: 99%
“…Based on an anatomical study by Choung et al (2016), this technique places the ulnar insertion (distal end) of the reconstructed tendon at 24% and ulnar insertion (proximal end) of the reconstructed IOM at 33% when compared with the length of the ulna. This places the reconstructed IOM more distally than in the normal IOM.…”
Section: Discussionmentioning
confidence: 99%